Setting the Scene: Partners' Leadership Behavior and Employees' Perceptions of Work Performance in Professional Service Firms. (November 2019) - Sandvik, Alexander M.; Selart, Marcus; Schei, Vidar; Martinsen, Øyvind L.
The effect of leadership behavior on work performance is highly context sensitive. We address this notion by investigating leadership behavior in one important but understudied organizational context—namely, professional service firms (PSFs). We examine how partners' leadership behavior in a PSF relates to employee self-leadership, creative climate, and work performance (N = 442). The results show that partners' consideration leadership behavior is positively related to employees' perceived work performance. Moreover, partners' consideration and intellectual stimulation leadership behavior are especially important drivers of self-leadership and creative climate in a PSF, which in turn are positively related to employees' work performance. Theoretical and practical implications are discussed.